Electrochemical Behavior of Natural Product as Green Inhibitor for Carbon Steel Corrosion in the Acidic Medium - Chong, Chao Sian (Universiti Teknologi PETRONAS, 2016)
The use of corrosion inhibitors has been widely employed in the industries to overcome the corrosion issues that costing a lot. However, these inhibitors are expensive and toxic. Lately, there are significant research on the use of natural products as green inhibitors due to their high efficiency, low toxicity and ecofriendly.Therefore, this project focused on the studying of feasibility of using aloe vera extract for carbon steel corrosion in acidic medium. The characterization of aloe vera extract was done by using Fourier Transform Infra-Red Spectroscopy to determine the successful extraction of active compound in aloe vera. The corrosion rate of carbon steel was tested in the presence and absence of aloe vera extract. The inhibition efficiency of using aloe vera extract at different concentration was also evaluated through gravimetric and electrochemical (potentiodynamic polarization) methods.